Comparison between recombinant bovine somatotropin and equine chorionic gonadotropin in timed artificial insemination protocols in Bos indicus cows under low body condition score - G. Gassenferth; V.M. Valle; F.A. Souza; M.G.T. Gomes; A. Gassenferth Júnior; G.V.A. Rosa; A. Bragato; E. Nogueira; L.E. Kozicki (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT This study aimed to evaluate the efficiency of recombinant bovine somatotropin (rbST) on pregnancy rate (PR), dominant follicle diameter (DFD) pre-ovulatory follicle diameter (DFPO), and follicular growth rate (FGR) in Bos indicus cows with low body condition score (BCS; mean = 2.3) subjected to fixed-time artificial insemination (FTAI) protocols. The females were divided into four groups: rbST group day zero (GbSTd0; n=31) received a progesterone (P4) intravaginal device + estradiol benzoate + rbST on d0 of the protocol; on d8, P4 was removed and PGF2 + estradiol cypionate were administered; on d10, FTAI was performed; GbSTd8; n=31) received the same treatment as GbSTd0, except rbST administration on d8; the control group (GC; n=42) received the same treatment as GbSTd0 but without rbST; equine chorionic gonadotropin group (eCGG; n=46) received the same treatment as GC + eCG on d8. Ovarian follicles were evaluated by ultrasonography (US) on d0, d8, and d10 of the protocols. PRs (at d35) and FGR between d8 and d10 of the protocol were calculated. PRs resulted 16.1%, 19.4%, 30.9%, and 43.4% in GbSTd0, GbSTd8, GC, and GeCG, respectively. eCGG PR differed significantly (P<0.05) from rbST groups but not to the GC; no difference was observed between rbST groups and GC. eCGG resulted in larger DFPO (11.2±1.5 vs. 9.6±0.5 in GbSTd0; 9.9±0.8 in GbSTd8; 10.1±1.3 in GC; P=0.0001) and greater FGR (2.20±1.03 vs. 0.93±0.50 in GbSTd0; 0.94±0.52 in GbSTd8; 1.17±0.64 in GC) (P<0.0001). It was concluded that rbST groups resulted in lower PR, FGR, and DFPO compared to eCGG in cows with reduced BCS; therefore, eCG is recommended for use in cows with low BCS in FTAI programs.